Hak-Hak Korban Pelanggaran HAM Yang Berat (Tinjauan Hukum Internasional dan Nasional) - Abdul Haris Samendawai (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The rights of the victim of serious human rights violence have been provided in various regulatory frameworks, however, conceptual flaws in the substance of law are sill apparent in our legal system. Such flaws in the substantial aspect is estimated to badly affect the implementation of the protection of the rights of victim of serious crimes against human rights, since the procedural aspects refer to the material aspect of law.This is a real challange which may push the related authorities and institutions to contribute to the effort for the protection and the development of human rights as well as the enforcement of law and justice among victims.Keywords: Rights Of Victim, The Serious Violence Against Human Rights, International Law